Antimicrobial leakage assessment of glass ionomer restoration enhanced by indium oxide nanoparticles suspension compared to conventional glass ionomer restoration in vitro study - Hasan, Dhuha M; Abbas, Maha J; Al-Ghurabi, Batool H; Başaran, Bahri (Journal of Baghdad College of Dentistry, 2025)
Background: Nanoparticles in restorative materials have enhanced oral hygiene and cleanliness by increasing the quality and usefulness of dental restorations, due to small sizes, high surface-area-to-mass ratios, antimicrobial activity and strong chemical reactivity. This study aimed to evaluate the microbial leakage of laser prepared indium oxide nanoparticles added to glass ionomer filling compared to conventional glass ionomer fillings in permanent teeth. Materials and methods: Indium oxide nanoparticles were prepared using laser ablation in liquid, their properties were examined by field emission scanning electron microscopy, Ultraviolet Visible spectrophotometer and mass concentration. A predetermined amount of glass ionomer has been added to attain a homogenous content. Leakage evaluation was performed using a microbiological infiltration technique with Streptococcus mutans as an indication. Results: revealed that spherical as well as uniform nanoparticles, with particle size less than 10nm. The absorption spectra have peaks between )260-300 (nm for differently prepared samples. It was found that prolonged time for microleakage with increased nanoparticles concentration with statistically highly significant difference (P<0.001), using the Mantel–Cox log‑rank test and the Kaplan-Meier plot. Conclusion: it can be concluded that adding Indium oxide nanoparticles to glass ionomer restoration makes it more effective in preventing microbiological leakage. It was considered an alternative to conventional glass ionomer restoration.